2011
DOI: 10.3171/2011.8.peds1131
|View full text |Cite
|
Sign up to set email alerts
|

Minicraniotomy versus bur holes for evacuation of chronic subdural collections in infants—a preliminary single-institution experience

Abstract: Object Various surgical interventions have been described to evacuate chronic subdural collections (CSCs) of infancy. These include transfontanel percutaneous aspiration, subdural drains, placement of bur hole(s) with or without a subdural drain, and shunting. Shunt placement typically provides good long-term success (resolution of the subdural fluid), but comes with well-known early and late complications. Recently, the authors have used a mini–osteoplastic cranioto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…[6] Subdural shunts have an inherent long-term potential morbidity. [5] Few cases may develop subarachnoid to subdural collection, which may be unrecognized and cause dependence on shunt. A second surgery may be required for its removal if it is not needed anymore.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] Subdural shunts have an inherent long-term potential morbidity. [5] Few cases may develop subarachnoid to subdural collection, which may be unrecognized and cause dependence on shunt. A second surgery may be required for its removal if it is not needed anymore.…”
Section: Discussionmentioning
confidence: 99%
“…A second surgery may be required for its removal if it is not needed anymore. [5] Klimo et al . [5] advocates most desirable procedure would be one that has the greatest chance of definitively treating the SDE as a single surgery with low risk of complications and without placing a shunt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include transfontanel percutaneous aspiration, subdural drains, placement of bur hole(s) with or without a subdural drain, and shunting. [10] While shunt placement typically provides good long-term success it has well-known early and late complications. The minicraniotomy technique may be superior to the burr-hole method, especially in children and was employed in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors still advocate the use of minicraniotomy given its good success rate, but this method is quite invasive. 3 Subduroperitoneal drainage has been the gold standard in our department for more than 15 years, and other studies have shown excellent results for this procedure, with more than 90% success. 4,5,9,17 The main advantages are a short period of hospitalization with continuous drainage and a low infection rate.…”
Section: Discussionmentioning
confidence: 99%